If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 5 = 4p + 14 Reorder the terms: 5 + 5p = 4p + 14 Reorder the terms: 5 + 5p = 14 + 4p Solving 5 + 5p = 14 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 5 + 5p + -4p = 14 + 4p + -4p Combine like terms: 5p + -4p = 1p 5 + 1p = 14 + 4p + -4p Combine like terms: 4p + -4p = 0 5 + 1p = 14 + 0 5 + 1p = 14 Add '-5' to each side of the equation. 5 + -5 + 1p = 14 + -5 Combine like terms: 5 + -5 = 0 0 + 1p = 14 + -5 1p = 14 + -5 Combine like terms: 14 + -5 = 9 1p = 9 Divide each side by '1'. p = 9 Simplifying p = 9
| 2y(2y+3)=6y(y-1) | | 18*(25*10)=330x | | 125=-5p-5(3+6p) | | 18*(25*10)=330 | | 8z=3x+5x | | -2(x-7)=4(x-2) | | ax-4=9 | | 4+7x-12=4x+12-x | | (q-8)=7q+5 | | -2x-12+3=3+x | | x*x+4y=(x+6)(x-2) | | 3x+3=-2(x-5) | | x^2+y^2+4xy+42x=0 | | 5x+20=3x-50 | | 6xy+xy= | | 2x+3x=20-2x | | 3x+20=5x+50 | | 3y-3x=10 | | N+3*5=3*2n-1 | | f(x)=x^2+y^2+4xy+42x | | -2n-5(n-6)=9 | | 8y-(2y-3)=9y+12 | | 3x^4-x+6=0 | | m=7-3(p-m) | | 52x+7=57 | | 3k/5+44=12k/25+18 | | 1.4x=28 | | 4(3+8)=16t | | -1.9+w=-4.8 | | A=2.3 | | F(x)=x^2+4x-7 | | 5(2x+1)+4= |